Christina Rossetti’s ‘Wounded Speech’ - Westerholm, Joel (Literature and theology, 2010)
Christina Rossetti’s religious poems have received much recent critical attention as aesthetic objects, historical documents and even as theological statements. I argue that those poems that are prayers should be read as ‘wounded speech’ as Jean-Louis Chrétien described, prayers that recognised the speaker’s own inadequacy, but neither received nor expected resolution. The lack of personal emotional fulfilment, however, revealed both the continuing need for God’s grace and the nature of the Christian life as communal.